Red Yeast Rice Preparations Reduce Mortality, Major Cardiovascular Adverse Events, and Risk Factors for Metabolic Syndrome: A Systematic Review and Meta−analysis - Yuan, Rong; Yuan, Yahui; Wang, Lidan; Xin, Qiqi; Wang, Ya; Shi, Weili; Miao, Yu; Leng, Sean Xiao; Chen, Keji; Cong, Weihong; , and BPNMI Consortium (Frontiers in Pharmacology, 2022)
Background: Metabolic syndrome (MetS) is characterized by the cooccurrence of obesity, insulin resistance, dyslipidaemia, and hypertension. Red yeast rice (RYR) preparations might be beneficial for the prevention and treatment of MetS. Objective: To implement a systematic review and meta-analysis to determine whether RYR preparations improve clinical endpoints and reduce risk factors for MetS. Methods: The PubMed, Cochrane Library, EMBASE, Scopus, China National Knowledge Infrastructure, Chinese VIP Information, and WanFang databases were searched for randomized controlled trials (published up to September 2020), and a meta-analysis was performed using fixed- or random-effects models. The primary outcome measures were mortality and major adverse cardiovascular events (MACEs), and the secondary outcome measures were biochemical parameters of blood glucose, blood lipids, and blood pressure. The registration number is CRD42020209186. Results: A total of 921 articles were identified, of which 30 articles were included in this article. RYR preparations group demonstrated significant improvements in MetS compared with control group. RYR preparations reduced the mortality and MACEs (RR=0.62, 95% CI [0.49, 0.78]; RR=0.54, 95% CI [0.43, 0.66]). In terms of blood glucose metabolism, fasting plasma glucose (FPG) (MD=-0.46 mmol/L, 95% CI [-0.71, -0.22]), haemoglobin A1c (HbA1c) (MD=-0.49, 95% CI [-0.71, -0.26]) and the homeostasis model assessment of insulin resistance (HOMA-IR) (MD=-0.93, 95% CI [-1.64, -0.21]) were decreased. Regarding the lipid metabolism, total cholesterol (TC) (MD=-0.74 mmol/L, 95% CI [-1.02, -0.46]), triglycerides (TG) (MD=-0.45 mmol/L, 95% CI [-0.70, -0.21]), and low-density lipoprotein cholesterol (LDL) (MD=-0.42 mmol/L, 95% CI [-0.78, -0.06]) were decreased, while high-density lipoprotein cholesterol (HDL) (MD=0.14 mmol/L, 95% CI [0.09, 0.20]) was increased. Regarding blood pressure, the mean arterial pressure (MAP) (MD=-3.79 mmHg, 95% CI [-5.01, -2.57]) was decreased. In addition, RYR preparations did not increase the incidence of adverse reactions (RR= 1.00, 95% CI [0.69, 1.43]). Conclusion: RYR preparations reduce mortality, MACEs, and multiple risk factors for MetS without compromising safety, which supports its application for the prevention and treatment of MetS. However, additional high-quality studies are needed to provide more evidence for the effect of RYR on MetS due to the heterogeneity in this study.